Indigenous peoples' positive experiences of culturally safe health care: a qualitative systematic review protocol. Issue 9 (11th September 2021) - Harding, Jillian; MacKinnon, Karen; Sangster-Gormley, Esther; Gordon, Carol
ABSTRACT: Objective: The purpose of this systematic review is to explore what is known about Indigenous peoples' positive experiences with culturally safe health care. Introduction: Research indicates that Indigenous people often experience stigma and discrimination from non-Indigenous health care providers when accessing health care services. One approach that has been put forward to address Indigenous health inequities is cultural safety. Studies have been conducted to identify what comprises culturally safe care for Indigenous people, however, many of these studies target the health care provider's perspective, rather than the perspective of the Indigenous person who is receiving the care. Inclusion criteria: This review will consider studies that involve Indigenous peoples' positive experiences with culturally safe health care from any study setting. Studies that present relevant qualitative findings including descriptions, examples, or stories about how a health care provider enacted cultural safety from Indigenous perspectives will be considered. Methods: MEDLINE, CINAHL, Embase, PsycINFO, First Nations Periodical Index, the Native Health Database, the Indigenous Studies Portal, and the Arctic and Antarctic Regions Database will be searched for published studies. The search for unpublished studies will include Google and Google Scholar, ProQuest Dissertations and Theses, and OpenGrey. Databases will be searched from 1988 onward and only studies published in English will be included. The JBI systematic review guidelines will be followed. The JBI process of meta-aggregation will be used to identify categories and synthesize findings. The ConQual approach will be used to assess confidence in the review findings. Systematic review registration number: PROSPERO CRD42020173003